Exploring the impact of load-shedding on Small, Micro, and Medium Enterprises operating within the City of Tshwane Metropolitan Area - Maswanganyi, Mkateko Cliffton (My University, 2024)
The purpose of this study was to explore the impact of load-shedding on Small, Medium and Micro Enterprises (SMMEs) operating within the City of Tshwane metropolitan area, with a view to formulating and recommending possible strategies that are likely to enhance the sustainability of these SMMEs. A qualitative study was conducted to establish the challenges faced by SMMEs due to load-shedding, to assess their current coping mechanisms during such times, and to explore their perspectives on possible strategies to mitigate the effects of load-shedding. The data was collected through semi-structured, in-depth interviews with 14 SMMEs (which were represented either by the owner, manager or business partner), two from each of the seven regions in the City of Tshwane. The findings revealed that load-shedding poses numerous challenges which threaten the sustainability of SMMEs. These challenges include capital, cash flow and profitability constraints, poor customer service and operational challenges. Despite these difficulties, the majority of SMMEs have developed various coping mechanisms to ensure business continuity, while a few have taken more drastic measures such as halting of nosiness operations. Common copying mechanisms utilised by SMMEs in this study include reliance on alternative electricity supply sources such as generators, leveraging of resources within their respective value chains and resorting to manual work. Some SMMEs have adapted and aligned their operational plans in line with the load-shedding schedules. The findings were corroborated by literature in Chapter 2. Furthermore, the study also explored SMMEs' views on future strategies to reduce the impact of load-shedding. Their views were that the South African government should subsidise their acquisition of alternative sources while prioritising to end load-shedding. Lastly, the study identified areas necessitating further research. These areas include investigating challenges contributing to the lack of government intervention in the SMME sector and finding effective and efficient coping mechanisms for SMMEs
Thesis (MBA.) -- University of Limpopo, 2024
Keywords: Load-shedding; Small, Medium and Micro Enterprises; City of Tshwane; Electricity; Small business -- South Africa -- Gauteng; Success in business -- South Africa -- Gauteng